Host control of human papillomavirus infection and disease. (February 2018) - Doorbar, John
Abstract: Most human papillomaviruses cause inapparent infections, subtly affecting epithelial homeostasis, to ensure genome persistence in the epithelial basal layer. As with conspicuous papillomas, these self-limiting lesions shed viral particles to ensure population level maintenance and depend on a balance between viral gene expression, immune cell stimulation and immune surveillance for persistence. The complex immune evasion strategies, characteristic of high-risk HPV types, also allow the deregulated viral gene expression that underlies neoplasia. Neoplasia occurs at particular epithelial sites where vulnerable cells such as the reserve or cuboidal cells of the cervical transformation zone are found. Beta papillomavirus infection can also predispose an individual with immune deficiencies to the development of cancers. The host control of HPV infections thus involves local interactions between keratinocytes and the adaptive immune response. Effective immune detection and surveillance limits overt disease, leading to HPV persistence as productive microlesions or in a true latent state. Highlights: Most papillomaviruses are associated with asymptomatic infections or self-limiting benign papillomas. The papillomavirus E6 protein restricts the infected basal cells ability to commit to differentiation. Viral gene expression is required at very low level in the infected basal layer. The viral E6/E7 proteins are deregulated in high-grade neoplasia and are involved in immune evasion. Papillomavirus disease is controlled by immune surveillance by skin-resident T cells.